La théâtralité du procès pénal : entre archaïsme et modernité - Sandrine Zientara-Logeay (Criminocorpus)
The original theatrical dimension of the criminal trials is striking both in the scenography and in the relation with the classical rules of tragedy. Yet it is now challenged due to two different ideas : proximity and economic efficiency. Yet judiciary dramaturgy is necessary for Justice to fulfill its mission – resolving conflicts due to private violence. It enables catharsis to work on all the actors of the judiciary scene, thus reinforcing social cohesion. Nevertheless, the theatrical aspect of criminal trials should be viwed in a more modern perspective. The change has already started and entails both a stronger adversarial system and new ethical and deontological requirements.